AB0510 The relationship between nailfold capillaroscopic assessment and telangiectasia score with severity of peripheral vascular involvement in systemic sclerosis. (23rd January 2014) - Yalcinkaya, Y.; Pehlivan, O.; Alpay, N.; Omma, A.; Erer, B.; Kamali, S.; Ocal, L.; Inanc, M.
Abstract : Objectives: To determine the association of nailfold videocapillaroscopy(NVC)findings and telangiectasia score with DU history and severity of peripheral vascular involvement(PVI) in Systemic Sclerosis(SSc). Methods: Fifty-nine SSc patients fulfilling Leroy and Medsger criteria were evaluated including Telangiectasia Score(TS)(Shah AA et al. J Rheumatol 2010), Modifiye Rodnan Skin Score(MRSS), Valentine Activity Scale(VAS) and Medsger Severity Scale(SS). Qualitative(early, active and late patterns) and semiquantitative assessments [capillary number(CN), irregularly enlarged capillaries(IEC), giant capillaries(GC), capillary ramifications(CR), microhaemorrhages(H), capillary array disorganisation(CAD) and microangiopathy evolution score(MES)]. was performed by NVC(Sulli et al. Ann Rheum Dis 2008) Results: The mean age of patients was 45.6 and 91, 5% were females. The mean duration of Raynaud's(RS), non-Raynaud symptoms(NRS), skin involvement(SI)(year) were 6.1±6.5, 3.1±2.0, 3.0±2.0 respectively. Of the patients 20(34%) were diffuse cutaneous, 35(59%) were limited and 4(7%) were sine-scleroderma;13(22%) were anti-centromere(+) and 29(49%) were anti-Scl70(+). DU history (DU+) was present in 27(46%) and telangiectases were present in 34(58%). When we compare DU- and DU + groups, the mean score of CN was 1.4±0.7 vs 2.0±0.5*(p<0.001), IEC was 1.4±0.7 vs 1.8±0.6**(p<0.05), MES was 1.8±1.0 vs 2.5±1.5**(p<0.05); early pattern was in 9 vs 1, active pattern was in 16 vs 14, late pattern was in 7 vs 12 patients. Current PVI grouped as Not Severe(SS;0-1)(n=43) or Severe(SS;2-4)(n=16). The frequency of severe PVI was 22% in females(12/54) and 80% in males(4/5). The mean values of TS, MRSS, VAS, SS were similar between groups. When we compare Not Severe and Severe groups, the mean score of CN was 1.5±0.7 vs 2.1±0.4*(p<0.001), MES was 1.8±1.1 vs 2.8±1.6** (p<0.05); early pattern was in 10 vs 0, active pattern was in 21 vs 9, late pattern was in 12 vs 7 patients. Conclusions: DU history and severe PVI in SSc was associated with capillary loss and microangiopathy. 'Early' NVC pattern was very rare in patients with DU history and was not found in severe PVI. Severe PVI in males was more frequent than females. Telangiectasia scores were not found to be related to PVI. NVC may be a helpful method in the assessment of SSc patients for PVI prognosis, warranting prospective studies. Disclosure of Interest: None Declared